Manipulating exercise and recovery to enhance adaptations to sprint interval training - Taylor, C. W. (2017)
Highly-trained athletes are accustomed to varied and high-volume based exercise stimuli and eliciting adaptation in individuals already possessing the necessary physiology to compete at the highest level is difficult. Therefore, identifying novel, potent and time efficient methods of achieving cumulative training stress is a continual quest for coaches and exercise scientists. This thesis examined the acute and chronic effects of manipulating exercise and recovery during brief all-out sprint cycling on adaptive responses favouring enhanced endurance capacity. Chapter 3 highlighted that low-volume non-work matched all-out sprint cycling, whether it be interval- (4 x 30 s bouts) or continuous based (1 x 2 min bout) provides a similarly potent stimulus for the acute induction of cell signalling pathways and key growth factors associated with mitochondrial biogenesis and angiogenesis in trained individuals. In line with manipulating recovery and in attempting to identify a novel and potent exercise intervention capable of giving athletes more return on their training investment, Chapters 4-6 investigated the efficacy of combining sprint interval training with post-exercise blood flow restriction (BFR). Firstly, it was demonstrated that BFR potentiates HIF-1a mRNA expression in response to SIT, tentatively suggesting an enhanced stimulus for hypoxia- and/or metabolic-mediated cell signalling associated with mitochondrial biogenesis and angiogenesis over SIT alone. Secondly, four weeks of SIT combined with post-exercise BFR provides a greater training stimulus over SIT alone in trained individuals to enhance VO2max (4.7 v 1.1 % change) and MAP (3.8 v 0.2 % change), but not 15-km TT performance. Finally, in response to four weeks of SIT combined with post-exercise BFR, an international female track sprint cyclist increased her CP and W by 7 and 2 % and VO2max and absolute MAP by 3 and 4 %, respectively. Through a combination of an acute in vivo molecular experiment, a training study and an athlete case study, this thesis has introduced a potentially potent and novel training concept that appears capable of augmenting aerobic capacity.